Curriculum Development for Indonesian Language Education Study Programs that Respond to the Merdeka Belajar Curriculum Learning Policy - Wahdaniah, Wahdaniah; Marhani, Andi; Fathiyah, Fathiyah (Indonesian Journal of Multidisciplinary Science, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) policy requires universities to redesign curricula to strengthen graduate adaptability and alignment with labor market demands. The Indonesian Language Education Study Program must respond by developing a curriculum that accommodates students’ right to study outside the program while maintaining core pedagogical and linguistic competencies. This study aims to develop an MBKM-responsive curriculum design and formulate course-conversion mechanisms aligned with Graduate Learning Outcomes (CPL). This research employed a Research and Development (R&D) method using a systematic development model. Data were collected through document analysis, Focus Group Discussions (FGD) involving lecturers, students, alumni, and graduate users, and expert validation. The findings indicate that: (1) the graduate profile was reconstructed into more flexible roles such as educators, researchers, and language entrepreneurs; (2) the revised curriculum structure accommodates 20–40 credits of off-campus learning activities, including educational internships, teaching assistance, and humanitarian projects; and (3) clear course-equivalence guidelines ensure the achievement of CPL in knowledge and specific-skills domains. In conclusion, the developed curriculum is valid and feasible, supporting flexible learning pathways while enhancing the relevance and competitiveness of Indonesian Language Education graduates in the era of disruption.